Implikasi Erupsi Gunung Agung Terhadap Pertunjukan Seni Tari Tradisional Di Kelurahan Ubud, Kecamatan Ubud, Kabupaten Gianyar, Bali - Sembiring, Bony Christianta; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2019)
Ubud is an area on the island of Bali which is known as a tourism area that is very popular with the cultures. This research purposes to analyze how the implications that occur as a result of the eruption of Mount Agung in 2017 on the traditional dance performances contained in the Ubud district. The method used to achieve the objectives in this research is using descriptive qualitative, namely by means of observation, interviews and documentation. The technique of determining informants in this study used a purposive procedure, the data were then analyzed using descriptive analysis. The results of the research analysis show the implications of the eruption of Mount Agung on traditional dance performances have an impact on the level of tourist visits which declined and there are also implications on the management system of dance performances contained in the Village of Ubud. The significant impact on the level of tourist visits occurred from March 2017 to December 2017 where there were no tourists visiting to watch traditional dance performances in the Ubud district because tourists were afraid of the outstanding issues of the eruption of Mount Agung. In addition there is an impact that occurs on the traditional dance performance management system in Ubud output, the changes include reducing the active days of the show, reducing ticket prices and reducing the duration of traditional dance performances in the Ubud district Key Words Natural Disasters, Implications of Eruption Mount Agung, Traditional Dance Performances in Ubud